A New Approach For Relationship Between Daylight and Indoor Illumination Level - Ayaz, Ramazan; Nakir, Ismail; Akca, Hakan; Ajder, Ali; Tanrioven, Mugdesem (IEEE, 2014)
In recent years, the studies on energy efficiency in both industry and academia increased visibly worldwide. As the result of these studies, DIN V 18599-4 is published in 2007. According to this pre-standard, calculation methods about building energy performance were prepared. During design process of building for high energy efficiency, pre-standard contains daylight supply factor. However these calculations are so complex for software development. Our studies on these calculations indicate that there are a lot of parameters which affect the results so realistic results cannot be obtained easily. Also, indoor lighting energy is affected from these results. These are disadvantages of this method. This study provides an alternative for calculation methods of daylight supply factor which is given in DIN V 18599-4 pre-standard. The relationship between global radiation on horizontal surface and building zone that has window is established and it is formulized empirically. Therefore, by using this formula the effect of daylight in windowed zone can be calculated. The number of calculations of this presented method is quite simpler and these calculations provide more realistic results than the pre-standard method in terms of indoor lighting energy.
Keywords: OFFICE BUILDINGS; HONG-KONG; PERFORMANCE; Energy & Fuels